mTORC1 activity repression by late endosomal phosphatidylinositol 3,4-bisphosphate - Marat, A.; Wallroth, A.; Lo, W.; Müller, R.; Norata, G.; Falasca, Marco; Schultz, C.; Haucke, V. (The American Association for the Advancement of Science, 2017)
Nutrient sensing by mechanistic target of rapamycin complex 1 (mTORC1) on lysosomes and late endosomes (LyLEs) regulates cell growth. Many factors stimulate mTORC1 activity, including the production of phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P3] by class I phosphatidylinositol 3-kinases (PI3Ks) at the plasma membrane. We investigated mechanisms that repress mTORC1 under conditions of growth factor deprivation. We identified phosphatidylinositol 3,4-bisphosphate [PI(3,4)P2], synthesized by class II PI3K b (PI3KC2b) at LyLEs, as a negative regulator of mTORC1, whereas loss of PI3KC2b hyperactivated mTORC1. Growth factor deprivation induced the association of PI3KC2b with the Raptor subunit of mTORC1. Local PI(3,4)P2 synthesis triggered repression of mTORC1 activity through association of Raptor with inhibitory 14-3-3 proteins. These results unravel an unexpected function for local PI(3,4)P2 production in shutting off mTORC1.